L’attività psichica del vivente in una prospettiva metapsicologica: uno studio dei casi di Dick e Robert - Cagna, Pamela (Metapsychologica - rivista di psicanalisi freudiana, 2024)
This article will resume, from a metapsychological perspective, some of the salient points of two infant clinical cases, those of Dick (Klein’s patient) and Robert (Lefort’s patient), on which an article was written in volume 1/2020 of this journal. The role of the self-preservation drives in the genesis of these two infant pathologies will be highlighted and will clarify that their importance is not only from the link with the somatic functions necessary for the survival of the individual, but also from the principal function they play both in the constitution of the ego-subject and in the relationship with the sexual drives. The reasons why hunger and all the other drives of the ego are considered in Freudian theory to be the trigger of psychic activity in the human being will be explained. Consideration will also be given to the criteria for evaluating the relevance or irrelevance of the elements that emerge during an anamnesis and the relationship between theory and clinical observation.